Jumbo Bacteriophages: An Overview - Yuan, Yihui; Gao, Meiying (Frontiers in Microbiology, 2017)
Tailed bacteriophages with genomes larger than 200 kbp are classified as Jumbo phages, and are rarely isolated by conventional methods. These phages are designated “jumbo” owing to their most notable features of a large phage virion and large genome size. However, in addition to these, jumbo phages also exhibit several novel characteristics that have not been observed for phages with smaller genomes, which differentiate jumbo phages in terms of genome organization, virion structure, progeny propagation, and evolution. In this review, we summarize available reports on jumbo phages and discuss the differences between jumbo phages and small-genome phages. We also discuss data suggesting that jumbo phages might have evolved from phages with smaller genomes by acquiring additional functional genes, and that these additional genes reduce the dependence of the jumbo phages on the host bacteria.